2004
DOI: 10.1016/j.virol.2003.11.030
|View full text |Cite
|
Sign up to set email alerts
|

PB2 amino acid at position 627 affects replicative efficiency, but not cell tropism, of Hong Kong H5N1 influenza A viruses in mice

Abstract: A single amino acid substitution, from glutamic acid to lysine at position 627 of the PB2 protein, converts a nonlethal H5N1 influenza A virus isolated from a human to a lethal virus in mice. In contrast to the nonlethal virus, which replicates only in respiratory organs, the lethal isolate replicates in a variety of organs, producing systemic infection. Despite a clear difference in virulence and organ tropism between the two viruses, it remains unknown whether the dissimilarity is a result of differences in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
255
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 352 publications
(278 citation statements)
references
References 22 publications
20
255
1
2
Order By: Relevance
“…After 48 h, the viability of the cells was monitored using a Cell Counting kit 8. It has been reported previously that a specific strain of H5N1 that is a highly pathogenic avian influenza virus causes extensive lung injury to mice and ferrets in experimental infections (Martin & Wurfel, 2008;Shinya et al, 2004;Tumpey et al, 2000). Despite the severity of experimental infection in animals, this highly pathogenic H5N1 subtype avian influenza A virus showed a lower level of efficiency of apoptosis induction in human macrophages by in vitro infection (Mok et al, 2007;Zhou et al, 2006).…”
Section: Resultsmentioning
confidence: 98%
“…After 48 h, the viability of the cells was monitored using a Cell Counting kit 8. It has been reported previously that a specific strain of H5N1 that is a highly pathogenic avian influenza virus causes extensive lung injury to mice and ferrets in experimental infections (Martin & Wurfel, 2008;Shinya et al, 2004;Tumpey et al, 2000). Despite the severity of experimental infection in animals, this highly pathogenic H5N1 subtype avian influenza A virus showed a lower level of efficiency of apoptosis induction in human macrophages by in vitro infection (Mok et al, 2007;Zhou et al, 2006).…”
Section: Resultsmentioning
confidence: 98%
“…In contrast to the non-lethal virus, which replicates only in respiratory organs, the lethal isolate was found to replicate in a variety of organs in mice, producing systemic infection (67). When tested in chicken embryo cells and a quail cell line, it was found that the identity of the PB2 amino acid at position 627 did not appreciably affect the replicative efficiency of the virus (67). However, viruses with lysine at this position instead of glutamic acid grew better in various types of mouse cells that were tested (67).…”
Section: Evolution Of Virulence Properties In Influenza Virusesmentioning
confidence: 87%
“…Yet another type of high-virulence character that has been found in some of those dangerous H5N1 strains that now circulate in birds is located in viral RNA polymerase complex genes (67,68). It was shown in one study that a single amino acid substitution, from glutamic acid to lysine at position 627 of the PB2 protein (which is one of the components of the viral RNA polymerase), was enough to convert a non-lethal H5N1 influenza A virus isolated from a human to a lethal virus in mice (67).…”
Section: Evolution Of Virulence Properties In Influenza Virusesmentioning
confidence: 99%
See 2 more Smart Citations